2022
DOI: 10.47191/ijcsrr/v5-i2-09
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Financial Literacy and Knowledge of Capital Market on Intention to Invest on Islamic Stock Exchange

Abstract: This study aims to find out the effect of financial literacy and knowledge capital market on intention to invest in Islamic stock exchange. Our study employed a quantitative method using survey techniques. Samples of this study were ninety-four students randomly selected from two departments of Islamic economy and banking within the Faculty of Islamic Economics and Business of State University of Islamic Studies Datokarama Palu, Indonesia. Our study found that financial literacy variables and knowledge of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
1
6
1
Order By: Relevance
“…The same thing was stated in research (Aryani, 2018), (Tanusdjaja, 2018), (Aini et al, 2019), which did not find a relationship between investment in the Islamic capital market and literacy. However, this study is different from the research (Malkan, 2022), (Jalari & Marimin, 2020), (Merawati & Putra Semara, 2015), (Syaifullah et al, 2019), (Herawati & Trisna, 2020), (Zaenal Arifin, 2022) which found that students' interest in investing had a positive impact due to literacy.…”
Section: Financial Literacy Of the Academic Community Of Iain Amboncontrasting
confidence: 94%
See 2 more Smart Citations
“…The same thing was stated in research (Aryani, 2018), (Tanusdjaja, 2018), (Aini et al, 2019), which did not find a relationship between investment in the Islamic capital market and literacy. However, this study is different from the research (Malkan, 2022), (Jalari & Marimin, 2020), (Merawati & Putra Semara, 2015), (Syaifullah et al, 2019), (Herawati & Trisna, 2020), (Zaenal Arifin, 2022) which found that students' interest in investing had a positive impact due to literacy.…”
Section: Financial Literacy Of the Academic Community Of Iain Amboncontrasting
confidence: 94%
“…It impacts the low utilisation of services and products by financial institutions. This condition also occurs in the Islamic capital market (Malkan, 2022;Sabir et al, 2021). Table 1 shows Islamic financial literacy in the financial services sector.…”
Section: Islamic Financial Literacymentioning
confidence: 81%
See 1 more Smart Citation
“…A comprehensive level of literacy can facilitate Generation Z's comprehension of the potential advantages and drawbacks associated with engaging in investment activities within the Islamic capital market (Malkan et al, 2022). Hence, it can be observed that Generation Z possesses a comprehensive awareness of the Islamic capital market, enabling them to recognize the periodic fluctuations in Islamic stock values.…”
Section: The Effect Of Islamic Capital Market Literacy On Investment ...mentioning
confidence: 99%
“…In other words, risk perception can explain why and how Islamic capital market literacy affects a person's intention to invest in Islamic instruments. Literacy increases an individual's understanding and confidence in Islamic investments (Malkan et al, 2022), while risk perception helps direct how they respond to the risks involved in such investments (Nguyen et al, 2017).…”
Section: The Effect Of Islamic Capital Market Literacy On Investment ...mentioning
confidence: 99%